Reward System and Employee Commitment: Evidence From Delta State Civil Service Commission, Asaba - Okolie, Ugo Chuks; EGBON, Thomastina Nkechi (Universitas Medan Area, 2024)
The most important and valuable organizational and institutional resource in both public and private services is the employee. This is primarily because, without the employee commitment, all other resources will be dormant. Against this backdrop, this study examined the impact of the reward systems on employee commitment in the Delta State Civil Service Commission, Asaba using useful primary and secondary data sources. We discovered that intrinsic and extrinsic rewards have a significant impact on employee commitment in the Delta State Civil Service Commission, Asaba. This finding is significant because it shows that the only way to engineer the civil service to play its crucially essential and facilitating role in the State's political and socioeconomic development is through the creation and secured intrinsic and extrinsic reward systems that are systematically planned and scientifically implemented. The study concluded that the Delta State Civil Service Commission, Asaba needs both intrinsic and extrinsic reward systems to foster greater employee commitment. Based on this finding, we recommended among others that Delta State Civil Service Commission's reward systems should be subject to modification to suit social conditions or changing circumstances in the society. This underscores the fundamental logic underpinning the many international initiatives launched by multinational corporations in Nigeria to promote organizational effectiveness, which assumes that management will pursue employees’ happiness voluntarily in the absence of robust organizational regulations and strict enforcement.